Students’ Perceptions of Smartphone-Based AI Tools in Arabic Vocabulary Learning: Evidence from Universiti Sains Islam Malaysia / Persepsi Mahasiswa Terhadap Penggunaan Alat AI Berbasis Smartphone dalam Pembelajaran Kosakata Bahasa Arab: Bukti dari Universiti Sains Islam Malaysia - Tiara Febrianti; Talqis Nurdianto; Yuslina Mohamed (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This research aims to: (1) analyze the perceptions of Arabic language students at USIM, specifically at FPBU, regarding the use of AI tools on smartphones for learning Arabic vocabulary, and (2) provide an empirical depiction of FPBU Arabic language students in improving vocabulary through AI applications. The study employs a quantitative method, using a survey approach with questionnaire instruments to analyze FPBU Arabic students at USIM related to the use of AI tools via smartphones. The instrument was validated by a USIM lecturer, Yuslina Mohamed. A quantitative approach was conducted with 70 Arabic students from FPBU USIM who actively used smartphones in their teaching and learning processes, selected through purposive sampling techniques. The quantitative data were analyzed using IBM SPSS Statistics 27, employing descriptive analysis, instrument validity tests (validity and reliability), and hypothesis tests (Pearson correlation). The findings indicate a significant relationship between AI tool usage and students’ perceived vocabulary improvement. Pearson's correlation test showed a positive and significant relationship between AI tool applications on smartphones and the enhancement of Arabic vocabulary (r = 0.846, p < 0.001). These findings suggest that Arabic AI tools are effective in improving vocabulary, memory retention, and confidence, aligning with current literature in digital Arabic language learning.Penelitian ini bertujuan untuk; (1) menganalisis persepsi pelajar bahasa Arab di USIM khususnya di FPBU mengenai penggunaan AI tools di smartphone untuk pembelajaran kosakata Arab, (2) menyajikan gambaran empiris mengenai penilaian dan pengalaman pelajar bahasa Arab FPBU dalam peningkatan kosakata Arab melalui aplikasi AI. Penelitian ini menggunaakan metode kuantitatif, yaitu pendekatan survei menggunakan instrumen kuisioner untuk menganalisis persepsi pelajar Bahasa Arab FPBU di USIM) terkait penggunaan AI tools melalui smartphone. Instrumen dalam penelitian ini sudah divaliditas langsung oleh dosen dari USIM yaitu Yuslina Mohamed. Pendekatan kuantitatif dilakukan terhadap 70 pelajar bahasa Arab FBPU USIM yang aktif menggunakan smartphone dalam pengajaran dan pembelajaran, dipilih menggunakan teknik purposive sampling. Data kuantitatif di analisis menggunakan IBM SPSS Statistic 27 melalui analisis deskriptif, uji kevalidan instrumen (validitas dan reabilitas) serta uji hipotesis (korelasi Pearson). Hasil analisis menunjukkan bahwa penggunaan aplikasi bahasa Arab yang rutin dan moderat berdampak signifikan pada peningkatan kosakata Arab. Berdasarkan uji korelasi Pearson, ditemukan hubungan positif dan signifikan penggunaan aplikasi AI tools di smartphone dan peningkatan kosakata Arab (r = 0,846, p < 0,001). Temuan ini menunjukkan bahwa penggunaan aplikasi AI tools Arab efektif dalam peningkatan kosakata, kemudahan mengingat, dan kepercayaan diri berbahasa Arab, sesuai dengan literatur terbaru di bidang pembelajaran bahasa Arab digital.